Disparity of Conviction Cases Blasphemy in Indonesia - Rahajaan, Jakobus Anakletus; Niapele, Sarifa (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2022)
Although freedom about religion has been guaranteed in Pancasila and the 1945 Constitution, in reality problems in society related to religion still occur, such as insults, degrading the beliefs of a group to problems related to the place of worship of a religion. The constitution, which guarantees freedom of expression, is widely abused so that there are unlawful acts, one of which is blasphemy. Judges with free and independent judicial power or the principle of freedom of judges, play an important role in realizing justice for society. However, the disparity of punishment in blasphemy cases has caused controversy about the freedom of judges who are considered not to meet the sense of justice of society. The focus of this study is on the disparity of punishment in blasphemy cases that go viral on social media. This is a descriptive research with a normative legal approach method (normative juridical) carried out by means of a literature study. The data collection tool used in this study is data in the form of document studies and literature tracing. The analytical knife in research is legislation, legal Grand Theory such as evidentiary theory and legal principles such as the principle of Equality before the Law, the Principle of Fair Trial, the principle of freedom of judges, the principle of contante justitie, the principle of justice, certainty and expediency of law and the principle of Nemo Judex Idoneus In Propria Causa. Based on the results of the study, it is understood that the principle of judge freedom is based on a negative evidentiary system, but with their beliefs and freedom, judges in deciding cases are often influenced by the judge's culture, namely the subjectivity of judges and the existence of intervention and intimidation which results in the disparity of punishment in blasphemy cases which is a fairly sensitive issue in Indonesia.